First report of Theileria buffeli/Theileria orientalis group and identification of piroplasms via Nested PCR-based RLB Hybridization assay in zebu cattle in the Western Highlands of Cameroon - Ngangnang, Ghislain Roméo; Aktas, Münir; Ulucesme, Mehmet Can; Désiré, Keptcheu Tchankwe; Anyangwe, Florence Fonteh; Payne, Vincent Khan (University of Tabriz, 2021)
Piroplasms infections are tick-borne diseases caused by haemoparasite of the genus Theileria or Babesia. They have a great impact on livestock production, especially cattle in sub-Saharan countries. However, data on the prevalence of bovine piroplasms and their genetic diversity are scanty in Cameroon. This study was aimed at highlight the species composition and determine the prevalence of piroplasms infecting cattle in the Western Highlands of Cameroon. To achieve this aim, blood samples from a total of 162 cattle were collected and examined using Reverse Line Blot hybridization (RLB) assay. The amplified hypervariable V4 region of the 18S rRNA gene of bovine piroplasms species, including Theileria parva, T. annulata, T mutans, T. velifera, T. buffeli/T. orientalis, T. taurotragi, Theileria sp (buffalo), Babesia bovis, B. bigemina, B. divergens, B. major and B. occultans was hybridized against species-specific probes. RLB hybridization assay revealed the presence of four piroplasms species with the overall prevalence of infection of 82.1%. Theileria velifera (71.6%) was the most prevalent species followed by Theileria mutans (43.21%), Theileria buffeli/T. orientalis (5.55%) and Babesia bigemina (3.7%). However, the study provided the first molecular evidence for the presence of T. buffeli/T. orientalis group species in cattle in Cameroon. Higher overall prevalence of infection of tick-borne pathogens was observed in this study area as well as the increase in prevalence and widespread of T. velifera and the observance of a new species of piroplasms. These results are an indication that special attention should be given to epizootiological investigations alongside well-adopted control programs. © 2021, Published by University of Tabriz.
Keywords: Babesia; Cameroon; Piroplasms; Prevalence; RLB; Theileria buffeli